EVALUATION OF THE ROLE OF CONTROL SYSTEMS ON FINANCIAL MANAGEMENT IN PUBLIC SECONDARY SCHOOLS: A CASE OF KAKAMEGA CENTRAL DISTRICT. - ATIENO, OMONDI MARGARET; SANGORO, OSCAR ONYANGO; ATIENO, JOSEPH ODUOR; ODONGO, TOBIAS OCHIENG; RONO, DR LUCY (IJRDO - Journal of Applied Management Science, 2015)
Governments around the world recognize the importance of education for personal and economic development and they invest huge sums of money on education annually. The huge investment on education by the government, parents and other stakeholders therefore calls for proper use and control of these resources. The GOK has put measures to ensure effective management of funds in schools like sending auditors to schools every year, insisting on public secondary schools keeping proper books of accounts, authorization of any payments by the BOG and non cash payment of tenders among other measures. Despite the control measures put in place some funds still get to wrong hands due to misuse and misappropriation. It is on the basis of the misappropriations that the study seeks to evaluate the role of control systems on financial management of public secondary schools in Kenya. The study will be based on Agency Theory and Reliability Model. The study will be guided by the Independent Variable - Control Systems, the Dependent Variable - Financial Management and the Moderating Variable- School Factors. Descriptive survey research design will be used. Census technique will be used to get information from principals’ bursars and other 8 members of the tendering committee in each school because they all hold key information and to avoid bias. The target population will be 190.This will consist of 19 principals, 19 bursars and 152 members of the tender committee from 19 public secondary schools in Kakamega central. Primary data will be collected by use of questionnaires and structured interviews, while secondary data will be collected through document analysis of financial records. Reliability of the research instruments will be tested through split half method. Validity will be tested through expert analysis of the research instruments and a pretest of the questionnaires in Kakamega south district. Both quantitative and quantitative data will be collected. The collected data will be coded and classified then entered into the computer to obtain descriptive statistics such as; frequencies, percentages, mean median, mode and variance by use of a tool such as SPSS. The data will then be presented inform of in form of tables, charts and graphs. The study may add to the existing literature on control systems, it may be used by policy makers to improve financial management in public secondary schools and may also help managers like principals and bursars to improve on their financial management practices.